Of the limitation and competence of TST and TRT in the edition of jurisprudence in the light of labor reform - Junior, Romeu Felix Menin (Revista Coleta Científica, 2018)
The theme of this article is: Of the limitation and competence of the TST and TRT in the edition of jurisprudence in the light of the labor reform. The following problem was investigated: The constitutionality or not of the alteration in the text of articles 8, § 2 and 702 of the CLT. The following hypothesis was considered: With the change of these devices, can we speak of the unconstitutionality in the creation and edition of TST and TRT summaries? The general objective is the specific objectives of this work are to seek the most coherent point of view based on the Guarantor and Leader point of view originating from the Constitution and passed the CLT based on the impact of labor reform on the court's jurisprudence, the limitation of Articles 8 and 702, jurisprudence as a source of law and the constitutionality and unconstitutionality of these articles. This work is important in the entire legal field, since changing this text makes it difficult to change and create jurisprudence and overviews, causing the Judiciary to limit itself, and the TST and TRT will not be able to restrict legally provided rights or create obligations that not provided for by law. This article concluded the unconstitutionality of these articles, for violating several constitutional principles and articles that are provided for in both the Constitution and the Code of Civil Procedure of 2015. Alleging that the entry of such provisions in the Brazilian legal system, without a doubt, would have a social setback, generating more unemployment and reducing rights, thus increasing the political, social and economic crisis. This is a qualitative theoretical research lasting six months.